(untitled) (Global Media Journal - German Edition, 2022)
Journalists and ethnographic researchers, such as anthropologists, sociologists or media scholars, have comparable ways of establishing initial contacts with people from their fields of interest. Due to the ongoing COVID-19 pandemic and consequential travel restrictions and social distancing, it has become increasingly difficult to access a field. Taking inspiration from social anthropologist Ulf Hannerz (2004, p. 226), who compared journalists and anthropologists as “neighboring groups engaged in a somehow parallel pursuit,” this article explores what researchers may learn from practitioners who conduct research without being on-site. Fed by various practical journalists’ experiences, the article aims to investigate how information and communication technologies (ICTs) and digitally mediated methods, such as online search tools and social media, can be used to establish contacts and gain trust remotely. Here, the relevance of these methods for accessing a field in general goes beyond the limitations imposed during the COVID-19 pandemic and can be of interest to all those who face difficulties of field access of any kind. Ultimately, this article reflects on corresponding ethical challenges that may arise while conducting research remotely.